Energy footprint assessment of sheep meat produced under two different farming systems in Tunisia - Ibidhi R.; Ben Salem H. (Innovation for sustainability in sheep and goats, 2019)
Energy is a major input for sheep production due to the intensification and mechanization of production technologies. Energy efficiency is one of the key indicators for developing more sustainable agricultural practices. However, the analysis of energy uses in different sheep production systems are scarce. In this context, this study had been set out to measure energy footprint (EF) of sheep meat production in two farming systems in Tunisia; the mixed sheep-cereal farming system (prevailing in Northern Tunisia, mainly the regions of Beja, Jendouba) and the agro-pastoral farming system (prevailing in southern Tunisia mainly the regions of Tataouine and Kebili) where farmers rely on the purchase of livestock feedstuffs from local markets. This study further considers differences in the two production systems to explore the causes of variation of EF in sheep meat production. A total of 80 sheep farms, were investigated, using data on direct (fuel and electricity) and indirect (structures, machinery, feed, fertilizers, pesticides, and seeds) energy inputs. EF was expressed as mega joule (MJ) per unit of live weight (LW). Results show that the average EF of all evaluated farms was 1.58 MJ/ kg of LW. Farms in the North had the highest EF (average 2.18 MJ/ kg of LW) for which energy use is distributed as following: 65% feed production, 15% water pumping for livestock watering and irrigation, 8% animal housing and lighting and 12% for transport. While the lowest EF was obtained in farms located in the south averaging 0.98 MJ/ kg of LW for which the energy use during feed production, water pumping for watering and irrigation, animal housing and lighting and transport were 15, 25, 9 and 51%, respectively. It is concluded that sheep meat production in the agro-pastoral farming system in Southern Tunisia is less energy demanding than in the mixed sheep-cereal farming system in the North of the country. This can be explained by the fact that feed production has the largest share of the total energy used by Northern’s farms. This means that efforts should be made to increase the energy efficiency of feed production and to increase feed use efficiency by animals.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)